Correction of speech disorders among preschool children under the influence specially designed dance classes - N. B. Petrenko; N. I. Vasilieva (Kazimierz Wielki University, 2017)
Petrenko N. B., Vasilieva N. I. Correction of speech disorders among preschool children under the influence specially designed dance classes. Journal of Education, Health and Sport. 2017;7(1):377-386. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.275958 http://ojs.ukw.edu.pl/index.php/johs/article/view/4245         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017.   Correction of speech disorders among preschool children under the influence specially designed dance classes   1N. B. Petrenko, 2N. I. Vasilieva   National University of Physical Education and Sport of Ukraine, Kiev1 Preschool educational institution of the combined type number 653, Kiev2 petrenko_natasha@ukr.net,  ceda@i.ua   Abstract Objective: To conduct a complex assessment of speech of preschool children with speech disorders before and after dance classes that were conducted using a specially designed program and to show effectiveness of this program. Matter: Categories of subjects: 4-5 years old children: the main group (n = 12) and control group (n = 18); 5-6 years old children: the main group (n = 14) and control group (n = 16). Children were examined at the beginning and at the end of a school year. Following speech features were evaluated on a 10-point scale: grammatical component (change in nouns by number); pronunciation of sounds (repetition of sentences); phonemic component (listening and visualization of a subject); lexical component (identification of objects and semantic generalization); syllabic structure of the word (number of syllables). Results: It was found that during the school year grammatical component of speech among 4-5 years old children increased by 18%, pronunciation of sounds increased by 14%, phonemic component - 16,4%, lexical component - 11%, syllabic structure of words - 8%. The control group also showed positive changes, but values were 2-3 times smaller. Positive changes in a core group of 5-6 years old children during the school year were even more significant than in a group of 4-5 years old children (17,2%, 16,6%, 21,9%, 19%, 17% ). Conclusions. Thus, positive changes in speech were set among 4-6 years old children with speech disorders under the influence of dance classes that were conducted using a correctional dance program. Keywords: preschool children, speech disorders, correctional dance program, dance classes.